Workers to capitalists: Repositioning Berlin's middle class - Weiss, H. (Economic Anthropology, 2025)
In the late 1920s, Siegfried Kracauer studied the then new middle class in Berlin, asking why they were not more disruptive of the structures that bore down on them. I ask the same about insecure professionals in contemporary Berlin, using Kracauer's book Die Angestellten as foil. Kracauer demonstrated that, in the 1920s, they still perceived themselves as workers, albeit white-collar and salaried workers. Berlin's professionals today perceive themselves and most everyone else as autonomous individuals possessing human capital that can appreciate or depreciate as the result of their actions. Work is but one of the sites in which a classless, self-formed identity can be cultivated and calibrated in all aspects of life. I show how this perception plays out in professionals' attitudes toward their work lives and after-work activities.